Vivências da maternidade durante a graduação : uma revisão sistemática - VIEIRA, Ailane Costa (2019)
The objective of this research was to understand the challenges and what kind of social support university students have in their daily life to achieve graduation, having to reconcile motherhood and university life. It is a systematic review, being the corpus scientific articles identified in the Capes Database, using the descriptors pregnancy and university student; mothers and university students, five articles published between the years 2009 and 2018 were selected. Family support, together with the existence of university day care centers, are alternatives for emotional and structural support for the academic mothers to complete graduation. It is concluded that women who become mothers during graduation are more likely to drop out of school.